A Rare Case of Cladophialophora bantiana Intracranial Infection: Highlighting the Utility of Next-Generation Sequencing in Diagnosis - Melissa Whitman; Nicole Vissichelli (Case Reports in Transplantation)
Cladophialophora bantiana is a dematiaceous fungi and the most common cause of cerebral phaeohyphomycosis. Here, we report a rare case of cerebral ventriculitis with development of a cerebral abscess due to C. bantiana diagnosed by cell-free DNA next-generation sequencing. Noninvasive diagnostics led to earlier disease identification and initiation of antifungal therapy, which has the potential to reduce mortality in this highly fatal disease.